Carcinoma of the apocrine glands with involvement of lymphatic vessels of the dermis: report of two cases - Jark, P. C. [UNESP]; Huppes, R. R. [UNESP]; Sierra, O. R. [UNESP]; Maria, B. P. [UNESP]; Raposo, T. M. M. [UNESP]; Werner, J.; Reis, C. C. V. dos [UNESP]; Bueno, C. M. [UNESP]; Laufer-Amorim, R. [UNESP]; Tinucci-Costa, M. [UNESP]; Nardi, A. B. de [UNESP] (Univ Austral Chile, Fac Ciencias Veterinarias, 2015)
Cutaneous inflammatory apocrine carcinoma is a non-common reported tumor which affects the skin causing multiple erosive lesions. The aim of this report is to describe two different cases of this atypical disease. Both cases presented with ulcerative and infiltrative lesions on cervical region. A surgical procedure was ruled out due to local infiltration and erosive condition. Case 1 was treated with bleomycin. Case 2 received just palliative treatment. In both cases the response was poor with survival times of 35 days and 15 days respectively. Clinical information about this disease is lacking on literature and more studies are warranted in order to describe better clinical presentation, treatment possibilities and prognostic.
Keywords: carcinoma; apocrine gland; dog